Student’s Difficulties in Translating Literary Texts: A Case Study of Indonesian EFL Undergraduates - Rahma Yunita; Akhmad Baihaqi; Dhafid Wahyu Utomo (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2026)
This study aims to investigate the translation difficulties encountered by second-semester students of English Department at a public university in Banten Province, Indonesia, in translating literary texts. This has particular focus on the following aspects: the preservation of the original style and tone; the interpretation of cultural references and idiomatic expressions; and the optimal balance between literal and free translation. The present study employed a case study, with data being collected through non-participant observation, a closed-ended questionnaire, and documentation of students' translated texts. The research study encompassed a total of 43 students and was guided by the principles of Newmark's (1988) translation theory. The findings indicate that students encounter various difficulties, including limited vocabulary, weak grammar comprehension, lack of contextual understanding, and unfamiliarity with narrative text features. Second-semester students face two major difficulties: (1) capturing style and tone, and (2) coping massive difficulty of using appropriate grammar in text. The consequence of these factors is the production of inaccurate and unnatural translations. The study concludes that enhancing students' translation competence and performance necessitates instruction that integrates theory and practice, with emphasis on linguistic and cultural competence, cultural sensitivity, and strategic translation methods.